The Bacterial Proteasome at the Core of Diverse Degradation Pathways - Müller, Andreas U.; Weber-Ban, Eilika (Frontiers in Molecular Biosciences, 2019)
Proteasomal protein degradation exists in mycobacteria and other actinobacteria, expanding their repertoire of compartmentalizing protein degradation pathways beyond the usual bacterial types. A product of horizontal gene transfer, bacterial proteasomes have evolved to support the organism’s survival under challenging environmental conditions like nutrient starvation and physical or chemical stresses. Like the eukaryotic 20S proteasome, the bacterial core particle is gated and must associate with a regulator complex to form a fully active protease capable of recruiting and internalizing substrate proteins. By association with diverse regulator complexes that employ different recruitment strategies, the bacterial 20S core particle is able to act in different cellular degradation pathways. In association with the mycobacterial proteasomal ATPase Mpa, the proteasome degrades substrates post-translationally modified with prokaryotic, ubiquitin-like protein Pup in a process called pupylation. Upon interaction with the ATP-independent bacterial proteasome activator Bpa, poorly structured substrates are recruited for proteasomal degradation. A potential third degradation route might employ a Cdc48-like protein of actinobacteria (Cpa), for which interaction with the 20S core was recently demonstrated but no degradation substrates have been identified yet. The alternative interaction partners and wide range of substrate proteins suggest that the bacterial proteasome is a modular, functionally flexible and conditionally regulated degradation machine in bacteria that encounter rapidly changing and challenging conditions.